Transjugular intrahepatic portosystemic shunt for hepatic sinusoidal obstruction syndrome with primary biliary cholangitis and alcoholic liver disease: a case report - Yang, Pei; Zhang, Feng; Wang, Feng; He, Yang; Wang, Yao; Qian, Lingrong (Frontiers in Medicine, 2025)
This article reports the case of a 73-year-old man with a 50-year history of long-term alcohol abuse (with daily intake of 250 g) combined with primary biliary cholangitis (PBC, AMA-M2 positive). The patient recently developed refractory ascites and manifestations of portal hypertension (hepatic venous pressure gradient, HVPG: 17.3 mmHg). Liver biopsy revealed characteristic sinusoidal dilation and congestion, fibrosis, and erythrocyte extravasation. It was discovered that the patient had a history of consuming Gynura segetum (a traditional Chinese herb) for 1 year. Based on clinical presentation and diagnostic findings, the final diagnosis included the following: (1) hepatic veno-occlusive disease/sinusoidal obstruction syndrome (VOD/SOS), (2) portal hypertension, (3) primary biliary cholangitis (PBC), and (4) alcoholic cirrhosis. After a poor response to medical treatment, a transjugular intrahepatic portosystemic shunt (TIPS) was performed, resulting in significant improvement (postoperative portal pressure gradient (PPG) decreased to 8 mmHg, with complete resolution of ascites). During a 6-month follow-up, liver function showed marked improvement, with the Child–Pugh score improving from class C (11 points) to class A (6 points).